Autokorelasi Spasial Demam Berdarah Dengue di Kota Tasikmalaya - Hubullah Fuadzy; Heni Prasetyowati; Elis Siti Marliyanih; Asep Hendra; Abdulah Mubarok Dadang (Loka Litbang Kesehatan Pangandaran, 2021)
Abstract. Tasikmalaya city is a high endemic dengue area which contributes to the high number ofdengue cases in West Java province. This study aims to analyze the geographic distribution patternof dengue infection at the village level and identify high-risk urban villages in Tasikmalaya City. Thisstudy analyzed the surveillance data of dengue cases in 2016–2020 which was routinely managed bythe Tasikmalaya City Health Office. Variables analyzed included date, patient’s name and address(villages). The map data in the form of a shape file (shp.) were obtained from BPS in 2019. The spatialautocorrelation analysis uses two approaches, (the global Moran Index and LISA). The results showedthat DHF cases in the Tasikmalaya city tend to increase in the last 5 years (2016–2020). The highestnumber of annual and monthly dengue cases occurred in 2020, (1,744 cases and 307 cases) withthe incidence rate peaked at 262.6561 per 100,000 population. The global Moran index test using asignificance level of 5 showed that there is a spatial autocorrelation between adjacent sub-districts ofdengue cases in Tasikmalaya city every year for the last 5 years (2016–2020, and cumulative). Thevalue of the global moran index (I) shows a positive correlation between urban villages to the numberof annual dengue cases for the last 5 years and is cumulative. It can be concluded that there aresimilarities in the characteristics of DHF cases in adjacent villages or the relationship between DHFcases tends to be spatially clustered.